Sustainable Ethical Tourism (SET) And Engagement Of Rural Communities In Hunan Province China (Journal of Namibian Studies : History Politics Culture, 2023)
The travel and tourism industry are often regarded as a promising business opportunity due to its rapid growth worldwide. Employment expansion, a broader economic foundation, population increase, social progress, and a renaissance in traditional arts are just some of the possible benefits of rural tourism in China. With unemployment in Hunan Province at an unprecedented level, their rural tourism industry is one area should be significantly considered. The Chinese government plan for promoting tourism may benefit from a greater responsibility for this industry. In order for tourism to play a significant role in China economic growth, the government needs to have effective and efficient governance of the environment. It is also important to raise awareness of the mindfulness issue so that sustainable tourism may place a stronger focus on mindfulness-based tourism products. This study highlights rural tourism, different types of rural tourism, and the positive effects rural tourism may have on local economies and national economic growth in the context of China 14th Five-Year Plan for 2021-2025 where China focuses on the effort to "open up the countryside," investing in rural regions with distinctive geographical or cultural characteristics in order to attract more tourists. The data and analysis presented in this paper are the result of an extensive literature research methodology that involved the use of an extensive number of published articles on the issue of rural tourism. The investigation focused on the interpretivist epistemology. In this study, the researcher discusses the issue in Hunan Province and offers a summary and assessment of its significance. The paper provides guidelines for achieving sustainable tourist growth in an ethical manner.